A novel MYORG mutation causes primary familial brain calcification with migraine: Case report and literature review - Song, Tingwei; Zhao, Yuwen; Wen, Guo; Du, Juan; Xu, Qian (Frontiers in Neurology, 2023)
Primary familial brain calcification (PFBC) is a disorder in which pathologic calcification of the basal ganglia, cerebellum, or other brain regions with bilateral symmetry occurs. Common clinical symptoms include dysarthria, cerebellar symptoms, motor deficits, and cognitive impairment. Genetic factors are an important cause of the disease; however autosomal recessive (AR) inheritance is rare. In 2018, the myogenesis-regulated glycosidase (MYORG) gene was the first to be associated with AR-PFBC. The present case is a 24-year-old woman with AR-PFBC that presented with migraine at the age of 16 years. Symmetrical patchy calcifications were seen in the bilateral cerebellopontine nuclei, thalamus, basal ganglia, and radiocoronal area on computed tomography and magnetic resonance imaging. AR-PFBC with migraine as the main clinical symptom is rare. Whole-exome sequencing revealed a compound heterozygous mutation in the MYORG gene, one of which has not been previously reported. Our case highlights the pathogenic profile of the MYORG gene, and demonstrates the need for exclusion of calcium deposits in the brain for migraine patients with AR inheritance.